AVALIAÇÃO DE RISCOS À SAÚDE HUMANA DEVIDO À PRESENÇA DE MACRO E MICROELEMENTOS EM SUPLEMENTOS PROTEICOS COMERCIALIZADOS NO BRASIL - Renan da Silva Vieira (2024)
Introduction: The consumption of protein supplements has become popular due to their benefits in protein biosynthesis and muscle mass gain. Athletes and gym-goers often consume Whey Protein (WP) at levels up to three times the recommended intake. However, few studies quantify the macro and microelements in these supplements, whose excessive intake can pose health risks. Objective: To assess the health risks associated with the consumption of macro and microelements in protein supplements marketed in Brazil. Methods: Samples of protein supplements were purchased from commercial establishments in Brazil. The concentrations of As, Cr, Cu, Cd, Hg, Mn, Pb, Se and Zn were quantified using Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES) after sample digestion. Health risk calculations were based on 30-year-old adults. Results: Concentrations of Cd and Hg were below the detection limit, while As, Cr, Cu, Mn, Pb, Se and Zn were detected. High concentrations of Zn, Cu, and Mn were observed. Chronic Daily Intake (CDI) calculations showed that Zn had the highest values, and As exceeded the Minimum Risk Levels (MRLs). The concentrations of Cd, Cr, Cu, Hg, Mn, Pb, Se and Zn were below the MRLs. However, the Hazard Index (HI) was greater than 1, indicating potential health risks for adults consuming 40 g/day. Conclusion: Elevated concentrations of Zn, Cu and Mn were found in all samples, and As exceeded safe levels in all WP samples. Prolonged consumption may cause health damage, highlighting the need for protein supplement monitoring.